Qualitative assessment in the third month of life allows for a better prognosis of the achievement of motor milestones versus assessment of pathological reflexes- prospective studies on Polish children - Surowińska, Joanna; Sobieska, Magdalena; Gajewska, Ewa (Frontiers in Public Health, 2023)
The characteristic feature of primitive reflexes is that they occur early in development and must expire at a well-defined age. The study was conducted prospectively on a group of 107 children (74 boys). The study population included 83 infants born on time (weight 3465 ± 395 grams) and 24 born prematurely (weight 2225± 793 grams). An analysis of motor development at three months of age consisting of a qualitative assessment (motor performance) and a check of reflexes was performed; at nine months, the child was checked for crawling and sitting down, and at 16 months